PENGOLAHAN LIMBAH CAIR TAHU MENJADI Nata de Soya DI KABUPATEN BANJAR, KALIMANATAN SELATAN - Pratika Viogenta; Amalia Khairunnisa; Samsul Hadi (Jurnal Bakti untuk Negeri, 2022)
One of the home industries located in Martapura, Banjar Regency, is a tofu factory. The raw material for making tofu is soybean seeds which are processed so that the main product is tofu. In addition to producing tofu, the factory also produces by-products in the form of liquid waste and solid waste. So far, liquid waste is not used, but solid waste is used as animal feed. For this reason, in the application of science and technology, skills are given in the form of training to utilize liquid waste from the tofu industry into a new product, namely Nata de Soya. Nata de Soya is a highly nutritious food product, especially in the content of carbohydrates, protein and crude fiber. The methods used in this training are lectures and demonstrations. The purpose of this program is to add insight and skills to tofu industry players and the community, especially around the factory in processing liquid waste into Nata de Soya products. The results of this study increased public knowledge about the consequences of improper waste disposal and processing as well as increased knowledge of fermentation technology products and even succeeded in utilizing the tofu industrial liquid waste into processed fermented food in the form of Nata de Soya.